Ready for Takeoff? The Potential for Low-Cost Carriers in Developing Countries - Schlumberger, Charles E.; Weisskopf, Nora (World Bank Group, Washington, DC, 2014)
The emergence of low-cost carriers (LCCs) has been a key catalyst for the development of the aviation industry in the last decade. Indeed, extensive research has been undertaken to analyze the business model and impact on the aviation sector and beyond. Despite recent developments in the LCC markets in Asia and Latin America, much of the research has been focused on developed countries. Therefore, the purpose of this book is to identify the premises and prerequisites of the LCC model, and assess whether this business model could be successful in other less-developed countries, in particular the countries of Sub-Saharan Africa. This book identifies various definitions that have been applied to describe the LCC business model. In essence the majority of researchers define LCCs as carriers which, through a variety of operational processes, have achieved a cost advantage over full-service carriers (FSCs). This cost advantage is, in most cases, translated to the consumers by a lower fare offering. Although many carriers are defined as LCCs, the LCC model has developed into many different variations since the original Southwest Airlines model, the first U.S. LCC, which began operations in the 1960s.